2002
DOI: 10.1034/j.1600-0765.2002.01612.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of cytotoxicity of nicotine in human periodontal ligament fibroblast cultures in vitro

Abstract: The use of tobacco products significantly contributes to the progression of periodontal disease and poor response to healing following periodontal therapy. The purpose of this study was to determine the effects of nicotine, a major component of cigarette smoking, on human periodontal ligament fibroblast (PDLF) growth, proliferation, and protein synthesis to elucidate its role in periodontal destruction associated with its use. Human PDLFs were derived from three healthy individuals undergoing extraction for or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
90
1
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(104 citation statements)
references
References 40 publications
10
90
1
3
Order By: Relevance
“…In in vitro experiments using human gingival fibroblasts (HGFs), it was found that nicotine treatment inhibited HGF proliferation in doses higher than 7.8 mM, and disrupted the microtubule and vimentin cytoskeleton in doses higher than 3.9 mM [Alpar et al, 1998]. Whereas in studies using human periodontal ligament fibroblasts, it was demonstrated that nicotine (≥ 25 μM) inhibited cell proliferation and protein synthesis (≥ 5 mM) in a dose-dependent manner [Chang et al, 2002]. In our study, HGFs were subconfluent or confluent before exposure to nicotine; therefore, the effect of nicotine on cell proliferation was not evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…In in vitro experiments using human gingival fibroblasts (HGFs), it was found that nicotine treatment inhibited HGF proliferation in doses higher than 7.8 mM, and disrupted the microtubule and vimentin cytoskeleton in doses higher than 3.9 mM [Alpar et al, 1998]. Whereas in studies using human periodontal ligament fibroblasts, it was demonstrated that nicotine (≥ 25 μM) inhibited cell proliferation and protein synthesis (≥ 5 mM) in a dose-dependent manner [Chang et al, 2002]. In our study, HGFs were subconfluent or confluent before exposure to nicotine; therefore, the effect of nicotine on cell proliferation was not evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…10 Nicotine has cytotoxic effects on periodontal ligament fibroblasts. 11 It also has inhibitory effects on periodontal cell proliferation and protein synthesis which result in impaired wound healing. 11 Smoking results in changes to vascular, 12 inflammatory, 13,14 immune 15 and healing responses.…”
Section: N B R I E Fmentioning
confidence: 99%
“…11 It also has inhibitory effects on periodontal cell proliferation and protein synthesis which result in impaired wound healing. 11 Smoking results in changes to vascular, 12 inflammatory, 13,14 immune 15 and healing responses. 10,11 There is considerable scientific evidence of its harmful long term effects on periodontal diseases.…”
Section: N B R I E Fmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Johnson and Guthmiller it increases the odds of developing periodontal disease 2 to 8 -fold, depending on the definition of disease severity and smoking dose. The exact mechanism of smoking action is still unknown however several mechanisms for negative periodontal effects of smoking are proposed which include decreased Ig G2 production [14], chronic reduction in blood flow and vascularity [15], increased prevalence of potential periodontal pathogens [16], shift in neutrophil function towards destructive activities [17], negative effects on cytokine and growth factor production [18], and inhibition of fibroblast growth, attachment and collagen production [19]. These mechanisms in one way or another, makes individuals more susceptible to periodontal disease and compromise the healing response.…”
Section: Classifications Of Dental Root Furcationmentioning
confidence: 99%